Jornalismo do século XIX : da Monarquia à República - Sousa, Jorge Pedro (2021)
During the Liberal Monarchy, the periodic press was essentially marked by political events that favored or restricted its diffusion. Legislation promoted or prohibited freedom of thought and expression, and newspapers experienced moments of great expansion or were violently repressed. Other axes for understanding the history of journalism in this period were social progress, the economy, and the levels of schooling, which remained at very low levels. The 19th century corresponded to the expansion of the press in Portugal and to the solidification of the culture of print and of the newspaper, with political and political-news journalism being the most relevant feature throughout this period. In the second half of the century, the transforming current of the industrialization of the press allowed the metamorphosis of political-news newspapers and the affirmation of news journalism. The circulation of information and periodicals has accelerated thanks to improved communications, which allowed for greater speed in the diffusion of events and also of newspapers. Social changes and new audiences led to progressive changes in the press and, in the transition to the new century, "modern journalism" gained space in Portuguese newspapers. Highly emotional events, reportages and sensationalist framings made their appearance, conquering new audiences and bringing the Portuguese newspapers into the industrialized press field.